1989
DOI: 10.1002/ptr.2650030310
|View full text |Cite
|
Sign up to set email alerts
|

Millettia thonningii molluscicide: A rapid knockdown cercaricide for schistosome cercariae

Abstract: suspensions of ground seed material from the West African legume, Millettiu thonningii, have previously been shown to be mollusacidal to schistosome-transmitting snails and thus potentially useful as a control agent for schistosomiasis. it is demonstrated here that Millettiu seed suspensions, in addition to their molluscicidal action, show considerable toxicity towards the infective c e r d a l stage of Schistosomu mumoni, a causative agent of human intestinal schistosomiasis. This toxicity consists of a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Consequently, a study on the activity of metal-exposed cercariae over time was initiated, especially as little is known about the effect of toxic substances on cercarial activity. Bioactive com-pounds from seeds of the West African legume Millettia thonningii induced an increased state of unresponsive immobility with increasing concentration in cercariae of Schistosoma mansoni (Squire andWhitfield 1989, Perrett et al 1994). Oshima et al (1992) demonstrated that the insecticide Cartap hydrochloride caused a gradual decrease in the activity of cercariae of Gigantobilharzia sturniae over a three hour period.…”
mentioning
confidence: 99%
“…Consequently, a study on the activity of metal-exposed cercariae over time was initiated, especially as little is known about the effect of toxic substances on cercarial activity. Bioactive com-pounds from seeds of the West African legume Millettia thonningii induced an increased state of unresponsive immobility with increasing concentration in cercariae of Schistosoma mansoni (Squire andWhitfield 1989, Perrett et al 1994). Oshima et al (1992) demonstrated that the insecticide Cartap hydrochloride caused a gradual decrease in the activity of cercariae of Gigantobilharzia sturniae over a three hour period.…”
mentioning
confidence: 99%
“…For each time-concentration point three replicates each utilizing at least 20 larvae were employed. Previous studies (Squire and Whitfield, 1989) have shown that the larval immobility induced by M. thonningii extracts is rapidly followed by death.…”
Section: Methodsmentioning
confidence: 93%
“…Aqueous extracts of the seeds of M. thonningii are highly toxic towards Biomphalaria glabrata and Bulinus truncatus snails (Evans et al, 1986) and snail egg masses (Tang, 1994). Squire and Whitfield (1989) and Perrett (1994) showed that aqueous and chloroform extracts also possessed potent concentration-dependent larvicidal properties with respect to schistosome miracidia and cercariae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation